Strategi Penguatan Kemandirian Ekonomi Pesantren Melalui Usaha Mikro Kecil Menengah - Solihin, Khabib; Azro'i, Imam (The Institute of Research and Service Community IPMAFA Pati, 2024)
The economic independence of Pesantren is one of the essential elements to support the role of Pesantrenin in providing educational services to the community. With economic independence, pesantren have financial resources for infrastructure development, infrastructure facilities, land expansion, and human resource development. One Pesantren with good economic independence in Pati Regency is the Pesantren Maslakul Huda. To find out the strategy for strengthening the economic independence of Pesantren through Micro, Small, and Medium Enterprises (MSMEs), this research was carried out using a qualitative method. The data collection technique uses triangulation, and the data analysis technique uses the Miles and Huberman model. The study results show that the Pesantren Maslakul Huda has an MSMEs-based business unit that plays a role in strengthening its economic independence. Through ten business units based on MSMEs, Pesantren-Owned Enterprises (BUMP) Maslakul Huda has succeeded in making a significant contribution to Pesantren's finances. The profit generated shows BUMP success in operating independently and providing crucial financial support for the operational needs of Islamic boarding schools, including for the development of infrastructure, facilities and infrastructure, human resource development, and others. Various business strengthening strategies have been implemented, including business development, business revitalization, addition of business units, and strengthening business management to realize sustainable economic independence of the Pesantren Maslakul Huda.